SOCIAL ACTOR REPRESENTATION ANALYSIS ON THE JAKARTA POST ONLINE NEWS OF PRESIDENTIAL ELECTION - Nuri Hidayatus Sholihah; Agwin Degaf (Journal of English for Academic and Specific Purposes (JEASP), 2020)
Social actor representation (SAR) is an interesting topic to be analyzed. Through the analysis of the social actor in the news, it invites readers to have critical thinking. In this research, the social actors proposed are the two pair candidates of the 2019 presidential election; Jokowi- Ma’ruf and Prabowo- Sandi. The research has consisted of two research questions. First is, how are the exclusion strategy used in the Jakarta Post online news to represent the social actor. Second is how are the inclusion strategy used in the Jakarta Post online news to represent the social actor. By using the theory of Van Leeuwen (2008), the result of this research shows that the journalist of the Jakarta Post mostly used inclusion strategy rather than the exclusion strategy.The identification strategy is mostly used to get support from the public. The identification is practical in figuring out and portraying a social actor. Journalists represent related to the identity that exists in a figure. The portrayal of the social actors through the identity attached to them can certainly invite more attention to readers.